DESAIN LANSEKAP SEAMEO BOGOR SEBAGAI KAWASAN AGROEDUWISATA - Rachmanto, Eurico Pratama; Hadi, Akhmad Arifin (Indonesian Society of Applied Science, 2024)
SEAMEO (Southeast Asian Ministers of Education Organization) BIOTROP is a center for the study of tropical biology under the coordination of the Ministry of Education, Culture, Research and Technology. Its activities include research, training, networking, and personnel exchange and information dissemination in tropical biology. More than 5000 visitors per year take advantage of the facilities and resources available at BIOTROP. To maximize this potential, BIOTROP has launched an Agro-Edu-Tourism program. The concept of Agro-Edu-Tourism was chosen because the main activities at BIOTROP are research in the field of tropical biology and agriculture in a broad sense, as well as tourism activities are considered as one of the most developing industries in the world. The aim of this research is to design the BIOTROP landscape that can be used as a facility for agroedutourism and enhance ecosystem services. The basic concept of this design is to maximizes the functions of the existing BIOTROP area, which currently serves as a tourist destination with a foundation in agriculture and education. The proposed basic concept is